Identification of viscoelastic material properties based on Big Bang-Big Crunch optimization method - (:unkn) unknown (JVE International, 2016)
An efficient identification method of the dynamic properties of viscoelastic damping materials using an optimization technique is proposed. A Zener fractional derivative model is used to describe the frequency-dependent dynamic characteristics of materials. In this study, the viscoelastic material is used in a Passive Constrained Layer Damping (PCLD) configuration in order to increase the shear deformation in the material. Mean Square Velocities (MSVs) of a clamped-free beam covered with a PCLD patch are measured in an environmental chamber at different frequencies and used as reference MSVs. The excitation force is performed thinks to a low mass magnet fixed on the beam and placed inside a coil subjected to an electrical current. Numerical MSVs are calculated using an equivalent single layer plate model with warping functions chosen to ensure continuity of transverse shear stresses and displacements layer's interfaces. ©JVE INTERNATIONAL LTD. VIBROENGINEERING PROCEDIA.DEC 2016.
Keywords: Big Bang-Big crunch; Passive constrained layer damping; Viscoelastic damping material